Impact of Violence on Health Reproduction Among Wives in Donggala - Nur, Rosmala; Mallongi, Anwar (Pakistan Journal of Nutrition, 2016)
Background: This study aims to investigate the impact of violence and the relationship between the socio-demographic factors and health reproduction problems. It is important to identify the groups (via screening) that are vulnerable to the impact of violence. Materials and Methods: This study was conducted in Sunju village (rural) and the Tanjung Batu sub-district (urban) of Donggala Regency Central Sulawesi. The participants included 94 women and the sample consisted of married women of child bearing age who were pregnant, puerperium, had experienced pregnancy or had given birth in the last 2 years and had experienced violence. Results: The results of this study revealed that the violence of a husband toward his wife that occurs during pregnancy and puerperium affects reproductive health and it is associated with pregnancy complications, unwanted pregnancy, sexually transmitted diseases, unsafe abortions, premature birth/low birth weight and loss of sexual desire. Additionally, there are differences in the health reproduction problems (pregnancy complications) according to the socio-demographics of the wives. Wives who suffered from pregnancy complications were more likely to be ), have a total of